1990
DOI: 10.1021/bi00466a010
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic quaternary structure of bovine .alpha.-crystallin as indicated from intermolecular exchange of subunits

Abstract: The structural bovine eye lens protein alpha-crystallin was dissociated in 7 M urea and its four subunits, A1, A2, B1, and B2, were separated by means of ion-exchange chromatography. Homopolymeric reaggregates of these subunits were prepared by removal of the denaturant via dialysis. It was found that subunits were exchanged upon incubation of mixtures of two homopolymers under native conditions. New hybrid species were formed within 24 h as demonstrated by isoelectric focusing. Moreover, native alpha-crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 41 publications
1
70
0
Order By: Relevance
“…In mammalian lens, ␣-crystallin exists as a heteroaggregate of ␣A-and ␣B-subunits and exists as a molar ratio of 3:1, although previous reports indicated that various ratios can be formed in vitro (53,54). The interaction between ␣A-and ␣B-crystallins has been investigated in several past studies.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian lens, ␣-crystallin exists as a heteroaggregate of ␣A-and ␣B-subunits and exists as a molar ratio of 3:1, although previous reports indicated that various ratios can be formed in vitro (53,54). The interaction between ␣A-and ␣B-crystallins has been investigated in several past studies.…”
Section: Discussionmentioning
confidence: 99%
“…in urea or guanidine HCl), and the ␣A-and ␣B-crystallins were reconstituted by removal of the denaturant (23,(37)(38)(39). The molecular weights of these reconstituted ␣-crystallins were always lower than that of native ␣-crystallin, indicating that the reaggregation is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Separation of ␣A-and ␣B-crystallins and Generation of Homoaggregates-The subunits of ␣-crystallin can be separated by a variety of methods (11,27,28). The subunits were separated on a C4 reverse phase column using a water-acetonitrile gradient containing 0.08% trifluoroacetic acid.…”
Section: Methodsmentioning
confidence: 99%